State-of-the-art review on reducing residential buildings’ risk to tornado hazards - Badmus, Afeez A.; Sutley, Elaina J. (Frontiers in Built Environment, 2025)
Tornadoes represent one of the most formidable natural hazards in the United States. Despite their frequent occurrence, they have received limited yet growing attention in engineering research and practice. Recent updates to the American Society of Civil Engineers/Structural Engineering Institute (ASCE/SEI 7-22) standards, incorporated into the 2024 International Building Code, mandate that Risk Category III and IV buildings in tornado-prone areas be designed to withstand tornado loads for the first time. Annually, over 1250 tornadoes are reported in the U.S., and post-disaster evaluations consistently reveal that residential buildings, including single-family, multi-family, and manufactured homes, account for two-thirds of the structural damage caused by tornadoes and most tornado-related deaths. However, these homes are not currently covered under the new provisions, leaving them vulnerable. This study reviews the research on mitigating tornado risk to residential buildings from a structural engineering perspective, including coverage on tornado formation, impact analysis and proposed mitigation strategies examined through numerical, experimental, and post-tornado field studies. Finally, the review covers community-level analyses and tornado resilience modeling using fragility methodology that supports risk-informed decision-making. Key findings reveal that current building codes and standards inadequately address tornado-specific loads, particularly for risk category II wood-frame structures. Additionally, this review highlights the need for improved fragility models that account for the unique characteristics of tornado forces, as well as enhanced mitigation strategies such as roof-to-wall connections and debris-resistant designs. These findings underscore the urgency of adopting tornado-resilient provisions in building codes and standards to reduce damage and fatalities in tornado-prone regions.